2015
DOI: 10.1007/s15010-015-0811-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia: a possible diagnostic marker of disease severity in visceral leishmaniasis

Abstract: It is hypothesized that hypertriglyceridemia could be of additional diagnostic benefit to assess the probability and severity of VL in endemic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…We observed that VL patients had low TC, HDL, and LDL levels and increased VLDL and triglyceride levels compared with the reference values for the general population according to age groups. Using an objective criterion that classifies patients by severity score, 9 this study clearly showed a correlation between high triglyceride levels and VL severity as hypothesized by Lal et al 4 Although the mean age of the patients classified as having severe disease was higher than that of those with nonsevere disease, triglyceride levels were higher in patients younger than 19 years, indicating that age is not a confounding variable for this association. Furthermore, the mean 6 SD of the lipid profile from normal individuals, in a previous study performed in Sergipe State in children and adolescent (12 6 3.9 y) shown a mean 6SD of total cholesterol 158 6 30.4 mg/dL, HDL 47.5 6 10.5 mg/dL, LDL 91.4 6 25.4 mg/dL and triglycerides 92.1 6 48.8 mg/dL.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We observed that VL patients had low TC, HDL, and LDL levels and increased VLDL and triglyceride levels compared with the reference values for the general population according to age groups. Using an objective criterion that classifies patients by severity score, 9 this study clearly showed a correlation between high triglyceride levels and VL severity as hypothesized by Lal et al 4 Although the mean age of the patients classified as having severe disease was higher than that of those with nonsevere disease, triglyceride levels were higher in patients younger than 19 years, indicating that age is not a confounding variable for this association. Furthermore, the mean 6 SD of the lipid profile from normal individuals, in a previous study performed in Sergipe State in children and adolescent (12 6 3.9 y) shown a mean 6SD of total cholesterol 158 6 30.4 mg/dL, HDL 47.5 6 10.5 mg/dL, LDL 91.4 6 25.4 mg/dL and triglycerides 92.1 6 48.8 mg/dL.…”
Section: Discussionsupporting
confidence: 70%
“…1 Studies have described hypocholesterolemia, alteration of lipoproteins, and hypertriglyceridemia in VL patients. [2][3][4][5] Mohapatra et al 3 and Lal et al 4 suggested using hypertriglyceridemia as a possible diagnostic and prognostic factor for the disease, but the first study included only nine patients and the second study, despite including a good number of patients, based its severity criteria on only the anemia and parasite load determined on a microscopic examination. None of these factors correlated the lipid profile with disease severity score.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these perturbances of the immune response, individuals infected with Leishmania species parasites have characteristic changes in serum lipid profiles. More specifically, human patients with VL have elevated triglycerides and reduced cholesterol levels ( 10 12 ) as well as decreased levels of some apolipoproteins ( 13 ). Additionally, at least two transcriptional profiling studies highlight lipid metabolic pathways among the “most relevant” pathways modulated by Leishmania species infection of mouse bone marrow-derived macrophages ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, some of these metabolic alterations are distal to the site of leishmaniasis lesions or even systemic. For example, serum triglyceride levels were significantly higher in VL patients (40), and a study of Indian VL patients showed that an increase in splenic parasite load came with a decrease in serum cholesterol (41). While systemic metabolic alterations are not unexpected in the case of VL, they have also been reported in CL.…”
Section: Leishmaniasesmentioning
confidence: 98%
“…In the context of leishmaniasis, several studies described above reported differences in selected serum or plasma metabolites compared to uninfected controls (40)(41)(42). The serum metabolome can also predict CL treatment success, with elevated pretreatment taurine, allantoin, N-acetylglutamine, and pyruvate predictive of successful pentavalent antimonial treatment (89).…”
Section: Avenues For Diagnosis and Patient Monitoringmentioning
confidence: 99%